O uso da cartografia como instrumento metodológico de análise da questão agrária na Bacia do São Francisco - Lima, José Hunaldo (2014)
This work had as objective to map the agrarian structure in the São Francisco basin, through the use of mapping as a methodological tool of analysis. A retrospective of the development of cartography and cartographic production around the basin was made. To answer the questions of the study, maps were made by using different variables, which helped to explana the agrarian issue in San Francisco. The starting point was the cataloging and analysis of the data in SIDRA, the Dataluta Network, in addition to other data in the INCRA. Maps of the environmental framework of the basin, of the socioeconomic issues, of the land structure, of the rural violence, of the mobilizations, the main crops. A map of the agricultural production space was elaborated, a resource that explains the formation of the different territories, and in them, the advancement of the agrohidronegócio in the basin responsable for generating conflicts over land and water. The data and maps have demonstrated how critical cartography, assist in the preparation of maps that explain the agrarian question in essence, became a consisted tool against the forces of capital in the countryside, in other words, when mapping ia usaed as a language tool it is capable of clarifying the essence of relationships. It can be shown, as in this study, the appropriation of natural resources and labor commodified by the processes of separation of man from the means of production in the São Francisco basin, ensure the profitability of capital in agrohidroterritórios there. Meanwhile, was possible to realize that the new territorialities made by agrohidronegócio at the time promoted the concentration and centralization of capital, ultimately strengthening movements that struggle for land and water.